Analysis of Marketing Strategies Towards Consumers of R-Rovit Reed Syrup Drink - Insani, Linggar Cahya; Lestari, Baroroh (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Nowadays there are so many soft drink producers which is somehow creating competition between producers in Malang and Batu as Batu is also one of the soft drink central production. But so far there is no producers make soft drink as the healthy soft drink package. This opportunity is first and it has started producing this healthy soft drink. In this research, the writer used quantitative method. The data was collected by spreading questionnaire and observing. The methods of analysis data in this research were regress linier, validity test and reliability, the classic test consist of normality, multicollinearity and heteroscedasticity, partial and test hypotheses simultaneously.The results of this multiple linear regression analysis show that prices, promotions, partially or simultaneously have a positive and significant effect on purchasing decisions. It can be concluded that purchasing decisions can be improved with prices which include, affordability of prices, suitability of prices with product quality, compatibility of prices with benefits, price competitiveness, for promotions that can be improved by promotions including promotional messages, promotional media, and promotion time.